ADVERSE IMPACT OF LOCKDOWN ON INDIAN SOCIAL AND PSYCHOLOGICAL BEHAVIOUR-A REVIEW - AGRAWAL, JYOTI; SAVALE, ABHILASHA; SHAKYAWAR , BHAVANA; YADAV, PRABINA; SIKARWAR, PRERANA; SHARMA, SHWETA (Innovare Journal of Education, 2021)
Due to high infectivity and death rates, the novel coronavirus 2019 (COVID-19) disease has caused worldwide social and psychological impact by causing mass hysteria, economic burden, and feelings of aloneness during illness and financial losses. Studies have identified “coronaphobia” as a byproduct of the pandemic, where people have an extreme terror of contracting the virus. Mass fear of COVID-19 has created an overabundance of psychiatric manifestations across almost all strata of society. In this review, the psycho-social impacts of COVID-19 have been studied. As a data source Pubmed and Google Scholar are searched with the following key terms- “COVID-19 and social impact,” “SARS-CoV2 and social effects,” “social impact of current Pandemic,” “Psychological impact of COVID-19,” “Psycho-social effects and Coronavirus.” Many current published data and news were extracted that provide significant data. Our study revealed that nationwide lockdowns and forced quarantine to fight against COVID-19 had produced acute panic, anxiety, obsessive behaviors, domestic abuse, hoarding, depression, post-traumatic stress disorder (PTSD) and food insecurity, including marked impairment in daily life functioning. The psycho-social aspects of older people, their caregivers, psychiatric patients and marginalized communities are badly affected in different ways and need special attention. From the present work, it can be concluded that there is an urgent need to find out effective ways to treat people and bring them out of fear and stress. As these symptoms are seen in large population sizes, we also need to study the long-term effects of these adverse effects on the mass level.